Demand uncertainty control based on the supply-driven coordination techniques in the Chinese catering service supply chain. (2016) - Gou, Juanqiong; Zhang, Shujun; Dai, Wei
Catering Service Supply Chain (CSSC) is a new supply chain of which Catering Service Integrator (CSI) is the core enterprise. The main purpose of CSSC is to provide supply chain services for different catering enterprises and restaurants. Instability, non-standardisation characteristics of the Chinese catering industry, the specialty and diversity of different restaurants lead to demand uncertainty of CSSC. This research classifies various uncertainty scenarios based on supply-driven theory. Supply-driven methodology is used to induce uncertainty sources to the supply-side, which can be controlled by CSI. Two strategies, service coordination with wide knowledge sharing and synchronous decision with intelligent inducement, are designed to induce and integrate customer demand to get the scale effect and to balance the personal demand. Correspondingly, this research presents the technology solutions, including supply-driven coordinative process, coordinative integration service platform and intelligent matching system, with the related information systems integration framework and data/knowledge integration natures.